Understanding in-car driver distraction: engagement with technology while driving - Trundle, Elisha (2017)
Most drivers are aware of the distracting effects and possible dangers of using their mobile phones while driving. Many studies have investigated this effect and although not all have found large changes in driver performance, all have concluded that nothing good can come from this behaviour. Without adding to the wealth of studies in this area, this PhD aimed to discover what kinds of attitudes drivers have towards these technologies, how these drivers behave in a ‘natural’ situation and how these drivers can be persuaded to cease using these technologies while driving. The first study was a large questionnaire aimed at measuring theory of planned behaviour constructs from drivers towards five in-car technologies; hand-held mobile phone use, hands-free mobile phone use, text messaging, MP3 player use and satellite navigation use. These identified that attitudes in particular are important predictors of intentions and behaviour. Regression models explained 38-76% of the variance in past behaviour for the five technologies showing that the theory of planned behaviour is a useful tool in understanding these kinds of behaviour. Studies 2 and 2.5 aimed to discover whether in-car technology could have a positive effect on driver performance with the use of a ‘risk monitor’. These results indicated that heart rate could be influenced in a simulator by instilling a sense of risk. Although no differences in driving variables were found, participants’ heart rates increased as accident risk increased, importantly showing that feelings of risk arousal can be induced in a simulated environment. Studies 3 and 4 used a novel design in which participants were given the choice to interact with an MP3 player and skip music that they personally did not like. Study 3 found that participants spent a significant amount of time looking away from the road when interacting with the device. However, no differences in lane deviations or speed deviation were found. Study 4 was then conducted to increase sample size and increase variability by introducing a second speed limit. Results showed that participants had a tendency to miss this speed limit due to interactions with the device. Main effects were found for standard deviation of speed, with the easy skip condition showing more variability than the control condition, possibly reflecting compensatory behaviours due to technology use. Eye data also showed the effects of technology use where glance durations were significantly longer while skipping compared to controls and were significantly longer during hard compared to easy tasks. Study 5 aimed to combine the risk monitor studies with the MP3 studies and create an environment where participants were free to interact with the device if they wished, but were also given some information on their risk of accident to take into account. Drivers on low risk roads interacted with the device more often than on high risk roads and spent more time listening to unpleasant music when the risk tone was present. In terms of driving measures, participants reached higher speeds when the tone was not present, while mean speeds showed a tendency to be lower when the tone was present. Study 6 was an intervention study which, informed by the results of study 1, created an intervention based on changing drivers attitudes towards technology use while driving. After the intervention was given, drivers completed a similar study to the MP3 experiments. This meant that not only could attitudes be measured at different time points, but actual behaviour relating to technology use could be measured. Theory of planned behaviour interventions are often criticised as they tend to measure behaviour by questionnaire rather than tangible measures of behaviour and so this was an advantage to this study. However, the intervention showed no significant effect on attitudes or MP3 music skipping behaviour. However, a significant correlation was found between the number of times a participant skipped and measures of driving violations. The challenge for future work will be to determine how attitudes can be changed towards technology use and whether further experiments may observe ‘natural’ behaviour in relation to different types of technology.